Pengaruh Kualitas Produk, Persepsi Harga, dan Promosi Terhadap Keputusan Menginap di The Sultan Hotel Jakarta - Vica Apriyanti; Yosafat Puji Hastoko (Human Capital Development, 2022)
This study aims to analyze the effect of product quality, price perception, and promotion on the decision to stay at The Sultan Jakarta Samples were taken of 100 respondents using accidental sampling technique. The data analysis method used in this research is multiple linear regression, validity test, reliability test, classical assumption test, and correlation analysis and coefficient of determination. The author uses a quantitative descriptive method by analyzing data using SPSS version 20. The results of this study indicate that product quality has a significant effect on decision stay, price perceptions have a significant effect on decision stay, and promotions have a significant effect on decision stay. Simultaneously the variables of Product Quality, Price Perception and Promotion have a significant effect on decision stay at The Sultan Hotel Jakarta. Keywords : Product Quality, Price Perception, Promotion, Decision Stay.